2009
DOI: 10.1159/000252978
|View full text |Cite
|
Sign up to set email alerts
|

<i>L</i>-Arginine and <i>L</i>-Nitroarginine Methylester Effects on Vasomotion in Isolated Rabbit Eyes

Abstract: Background/Aims: Although nitric oxide (NO) has been shown to be essential for maintaining the basal blood flow in the retina and optic nerve head, its exact role in vasomotion is still controversial. This study investigated L-arginine (L-Arg) and N-nitro-L-arginine methylester (L-NAME) effects on vascular reactivity in a model of isolated rabbit eye. Methods: Rabbit external ophthalmic arteries (n = 12) in a head-mounted preparation were cannulated and perfused with warmed Tyrode solution. The effect of intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…This is also supported by the observations that l -arginine uptake, rather than the intracellular l -arginine concentration, is important for NO production in endothelial cells [25]. Indeed, in isolated rabbit eyes, administration of l -arginine decreases ocular vascular tone [26], supporting a major role for l -arginine uptake and NO release in endothelium-dependent relaxation in retinal arterioles.…”
Section: Introductionsupporting
confidence: 56%
“…This is also supported by the observations that l -arginine uptake, rather than the intracellular l -arginine concentration, is important for NO production in endothelial cells [25]. Indeed, in isolated rabbit eyes, administration of l -arginine decreases ocular vascular tone [26], supporting a major role for l -arginine uptake and NO release in endothelium-dependent relaxation in retinal arterioles.…”
Section: Introductionsupporting
confidence: 56%
“…In the decomposition of the signal obtained in the ex vivo models, there were no bands present in the HF or LF region due to abolition of autonomic influences, so the myogenic vascular responses were due to autoregulatory mechanisms as has been demonstrated elsewhere [13,14,15]. …”
Section: Discussionmentioning
confidence: 69%
“…These spontaneous diameter changes have been shown in all tissues hitherto studied, including the choriocapillaris, 4 and both in vivo and in vitro studies in the retina have shown that the phenomenon depends on NO-induced synthesis of cyclic guanosine monophosphate (GMP). [5][6][7] The accompanying oscillations in oxygenation have been recorded both in the retina 7 and in the optic nerve. 9,10 Vasomotion has been found to be disturbed outside the eye in patients with diabetes mellitus, 11 and disturbances in vasomotion has been proposed to be involved in the pathogenesis of diabetic retinopathy.…”
Section: Spontaneous High Frequency Diameter Oscillations Of Larger Rmentioning
confidence: 99%